Trypanosoma cruzi DNA in heart tissues of patients with end-stage chronic Chagas heart disease - Vigliano, Carlos (2004)
Trypanosoma cruzi DNA in cardiac lesions of Argentinean patients with end-stage chronic chagas heart disease.Schijman AG, Vigliano CA, Viotti RJ, Burgos JM, Brandariz S, Lococo BE, Leze MI, Armenti HA, Levin MJ.Laboratorio de Biologia Molecular de la Enfermedad de Chagas, INGEBI, Consejo Nacional de Ciencia y Tecnologia, Department of Fisiology, Celular and Molecular Biology, F. CEyN, University of Buenos Aires, Buenos Aires, Argentina.The extent of inflammation, fibrosis, and progression of chronic Chagas heart disease (cChHD) was associated with persistence of parasite DNA in cardiac lesions of necropsies or explants from Argentinean cChHD patients. A Trypanosoma cruzi-based polymerase chain reaction showed a positive result in 1) 15% of cardiac sections with less than 10 mononuclear inflammatory cells/high-power field (440x) (MNC/HPF), 89% with 10-19 MNC/HPF, and 100% with more than 20 MNC/HPF (P < 0.0001); 2) 33% with less than 10% fibrosis, 79% with 10-19% fibrosis, and 100% with more than 20% fibrosis (P < 0.01); 3) 25% of specimens from patients classified in Kuschnir groups 0 and I, 70% in group II and 90% in group III (P < .001); and 4) 45% and 90% of the specimens from cChHD patients without or with heart failure, respectively (P < 0.01). These findings stress the role of the parasite in pathogenesis and disease progression of cChHD.